Caracterização populacional e molecular, e seleção de Trichoderma spp. para biocontrole de Fusarium sp. em crisãntemo - Menezes, Josiane Pacheco (2007)
Trichoderma spp. is one of the most researched fungi as biocontrole agent of diseases, being antagonistic to several phytopathogens in different crops. The soilborne pathogen Fusarium oxysporum causes wilt in several crops, including chrysanthemum, is of difficult control, due mainly to its survival capacity in the soil for long periods, even without the presence of the host. Studies about the population dynamics of Trichoderma spp. and Fusarium spp. and of the associated native microbiota they necessary, especially, to observe the impact of the biocontrols addition in the soil. Ornamental plants, such chrysanthemum, are cultivated in Rio Grande do Sul, but they are susceptible to several diseases, among them, the wilt of Fusarium oxysporum, mainly in protected environment. Aiming at the biocontrol of the wilt caused by F. oxysporum in chrysanthemum, as well as the understanding of the population dynamics of the microbiota in this patossystem, this work had for objectives: to study the dynamics of the fungic population present in soil used in the chrysanthemum cultivation in greenhouse in presence and ausence of wilt symptoms; to select and identify isolates of Fusarium pathogenic to chrysanthemum; to isolate and select antagonists, of the gender Trichoderma, effective in the biocontrol of Fusarium oxysporum in vitro; to verify, in vivo, the effectiveness of the antagonists tested in vitro in control of F. oxysporum; to evaluate the survival of Trichoderma sp. in substract with the incorporation of biological products of the fungus; to analyze the population dynamics of Fusarium sp. and Trichoderma sp. in sterilized soil and with addition of bioprotector; to identify the isolates of Trichoderma sp. used in the biocontrol of the pathogen; to evaluate the effect of administrations of Trichoderma sp. in non-target organisms. The soil sampling cultivated with chrysanthemum in greenhouse showed variation in the fungic populations of Trichoderma sp. and Fusarium sp. as a function of the occurrence of wilt symptoms in plants. Of the isolates of Fusarium sp. inoculated, 25,3% were pathogenic to chrysanthemum, which were found at points with visible symptoms of the disease on the plants. The biological products of Trichoderma sp. used varied in their effectiveness in the control of the wilt of chrysanthemum, being able to reach 100% of biocontrol as in the case of isolate UFSMT15.1. The desinfestation of the soil with methyl bromide reduced the population of Trichoderma, Fusarium and other fungi. The incorporation of the biological products in the soil promoted population growth of Trichoderma sp. and inhibited the growth of Fusarium sp. The molecular characterization of the isolates of Trichoderma indicated that the region of ITS of isolates UFSMT15.1, UFSMT16 and UFSMT17 of Trichoderma sp. it presents a simple band with a fragment of approximately 600 bp and the isolate UFSMT17 present high phylogenetic similarity with the specie Trichoderma aureoviride. In the rats treated with biological product of active Trichoderma sp., no viable spores of the fungus werw found in the sampled tissues after a hour of the administration of the bioproduct.